The Role of Iranian Cinematic Portraits of Prophet Muhammad(Peace be Upon Him): A Critical Reassessment of its Sources and Its Theologically Problems in the Perspective of Islamic Sharīʿah - Muhammad Asad Latif (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
They started their agenda, and their religious affairs began to get involved in financial aid, and then in the same way Prophet Moses. From time to time on every prophet (wherever possible) they filmed internationally and nationally. Even producers of Motion Pictures issued a penal code stating that immoral material would not be displayed on any prophet or religion, and that it had the signature of the regular Catholic Church, but later this issue was increased. Hollywood influenced Iranian productions, and Mustafa Akkad promoted similar films, which led to similar actions by later producers.Sunnis are scorned in the Hollywood because of the same disgusting act of Iranians. It is not permissible in any case to insult the prophets and present them in a negative form, moreover in novels, books, or movies. The following are some of the reasons why the prohibition of filmmaking and photography is proved in the best and most perfect way. In the same way, superstitions prove and promote Sharīʿah intuition.in this paper will figure out those offensives false conception of causation that effecting on these parables through the Islamic Sharīʿah.